2009
DOI: 10.1002/jnr.22329
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of CD133+CD34 cells in healthy individuals following whole‐body acupuncture for spinal cord injuries

Abstract: Acupuncture can alleviate symptoms of spinal cord injuries (SCI). The underlying mechanism, however, is unknown. We hypothesized that stem cells could be mobilized by acupuncture. Therefore, we enrolled 14 healthy study participants using acupuncture points for the treatment of SCI. The frequency of CD133 and CD34 cells in peripheral blood and the serum concentrations of matrix metalloproteinase (MMP)-9, brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), and interleukin-6 were determined befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…PD patients who received acupuncture for 3 months showed increased levels of BDNF in peripheral blood. However, in the spinal cord injured patients, BDNF levels were found to be decreased 48 h after acupuncture [77,78,85]. Thus, the potential function of blood BDNF in spinal cord injury remains uncertain.…”
Section: The Potential Mechanisms Of Acupuncture With Regard To Modulmentioning
confidence: 99%
See 1 more Smart Citation
“…PD patients who received acupuncture for 3 months showed increased levels of BDNF in peripheral blood. However, in the spinal cord injured patients, BDNF levels were found to be decreased 48 h after acupuncture [77,78,85]. Thus, the potential function of blood BDNF in spinal cord injury remains uncertain.…”
Section: The Potential Mechanisms Of Acupuncture With Regard To Modulmentioning
confidence: 99%
“…Early data have demonstrated that BDNF is stored in human platelets and released by physical stimulation [85]. However, the platelet number in hunman serum remained constant after acupuncture while BDNF levels decreased, although levels of BDNF-related neurotrophin NGF and other cytokines remained unchanged [78]. Although blood BDNF level has been reported to be associated with the time of acupuncture, inflammation and stress, the underlying mechanism for such relationship is still unclear.…”
Section: The Potential Mechanisms Of Acupuncture With Regard To Modulmentioning
confidence: 99%
“…Acupuncture has been used to treat dogs and cats for around 10 years, mainly for musculoskeletal problems [14], low back pain [17], knee osteoarthritis [18], tension-type headache, and migraine [19, 20]. Interestingly, acupuncture has been shown to mobilize stem cell compartments such as CD133+34− cells [21]. …”
Section: Introductionmentioning
confidence: 99%
“…The use of this discipline in both oncology and in palliative care is scientifically supported and is employed by world-renowned hospitals in the US, including Memorial Sloan-Kettering Cancer Center, MD Anderson Cancer Center and Dana Farber Cancer Institute [7]. According to the latest studies, acupuncture effects in oncological applications are ascribable to systemic and biochemical reactions and bioelectrical modifications that act to decrease release of inflammatory cytokines [8], reduce T-cell activation [9], increase adenosine release [10] and alter neuropeptide-based activation, opioid peptide-based activation, peptidic hormone activation or stem-cell activation [11].…”
Section: Introductionmentioning
confidence: 99%